Linear cultural heritage eco-cultural spatial system: A case study of the Great Tea Route in Shanxi - Tianyi Zhang; Xinyi Chen; Tianqi Liu (Frontiers of Architectural Research)
The preservation of linear cultural heritage currently stands as a critical issue within the realm of global cultural heritage protection. The integration of cultural and ecological factors, as well as protection policies and implementation strategies, are facing great challenges. In 2019, the linear heritage “the Great Tea Route” was added to the Tentative List of China's World Cultural Heritage, underscoring its cultural and ecological significance. This study presents the construction of an expansive cultural and ecological corridor network across the Shanxi Province section of the route, employing morpho-spatial pattern analysis, the MaxEnt model, and the MCR model to effectively integrate cultural and ecological resources. And explores the establishment of cultural landscape nodes and the enhancement of cultural and ecological services, advocating a community co-construction model. This not only facilitates the development of a corridor-based economy but also addresses administrative challenges, thus promoting the preservation and management of cultural and ecological resources. The network developed comprises 43 cultural ecology points, 86 cultural source points, and 21 ecological sources, forming a foundation for the corridor's conservation and use. This study aims to provide new insights for the sustainable management of linear cultural heritage and promote the comprehensive protection of resources.